Efficient Itaconic acid production via protein–protein scaffold introduction between GltA, AcnA, and CadA in recombinant Escherichia coli. (22nd March 2019) - Tran, Kim‐Ngan T.; Somasundaram, Sivachandran; Eom, Gyeong Tae; Hong, Soon Ho
Abstract: Itaconic acid, which is a promising organic acid in synthetic polymers and some base‐material production, has been produced by Aspergillus terreus fermentation at a high cost. The recombinant Escherichia coli that contained the cadA gene from A. terreus can produce itaconic acid but with low yield. By introducing the protein–protein scaffold between citrate synthesis, aconitase, and cis‐aconitase decarboxylase, 5.7 g/L of itaconic acid was produced, which is 3.8‐fold higher than that obtained with the strain without scaffold. The optimum pH and temperature for itaconic acid production were 8.5 and 30°C, respectively. When the competing metabolic network was inactivated by knock‐out mutation, the itaconic acid concentration further increased, to 6.57 g/L.